PENGARUH PROFITABILITAS, INVESTMENT OPPORTUNITY SET DAN CASH RATIO TERHADAP DIVIDEN KAS - Astuti, Siti Puji; Aziz, Alfida (Fakultas Ekonomi dan Bisnis, Universitas Pembangunan Nasional Veteran Jakarta, 2015)
This study aimed to examine the effect of Profitability and Investment opportunity set and the cash ratio of the Cash Dividend on wholesale services firm (durable and non durable goods), retail trade and restaurant, hotel and tourism that are listed in the Bursa Efek Indonesia 2011-2013. The population in this research study number 76 service companies listed in Bursa Efek Indonesia. Data obtained from the financial statements for 2011 to 2013 that has been published. The analysis technique used is multiple linear regression and hypothesis testing with a constant 5%. The results showed that a significant and positive effect on profitability, investment opportunity set variables and no significant negative effect and variable cash ratio and no significant negative effect. The coefficient of determination R square shows at 0.298 or 29.8% explained that the variable cash dividends is explained by the variable profitability, investment opportunity set and the cash ratio while the remaining 0,702 or 70.2% explained by other variables.